Report on the 15th Polish Conference on the “Humanistic Ecology” Series: “Anthropological and Natural Aspects of Consumption of Moderation and Excess” (Warsaw, 27 October 2021) - Ryszard F. Sadowski (Studia Ecologiae et Bioethicae)
The abstract is not available.